Late triassic detrital zircon ages from the nunatak Viedma on the southern patagonian icefield - Suárez, Rodrigo Javier (2018)
The Nunatak Viedma on the Southern Patagonian Icefield has been historically considered as a volcanic center based onmorphological evidence. Field explorations carried out at the summer of 1958-1959 by Eric Shipton determined its metamorphicsedimentarynature. However, the age of these rocks is unknown as well as its possible correlation with others metamorphiccomplexes that constitute the basement of southern Patagonia. In order to constrain the maximum depositional age of theprotoliths and to identify the provenance sources, three samples of metasedimentary rocks were taken from the southern outcropsof the Nunatak Viedma to analyze detrital zircons by LA-ICP-MS U-Pb method. The age distribution of detrital zircon grainsallowed identifying groups of Paleozoic-lower Mesozoic (65%), Proterozoic (34%) and isolated Archean ages (1%). The peaksof Paleozoic-early Mesozoic detrital ages define main groups in Lower Cambrian (~520 Ma), Lower-Middle Ordovician (~480-460 Ma), Upper Devonian (~380 Ma), Permian (~290-260 Ma) and Triassic (~235-225 Ma). Besides the maximum depositionalage was constrained at 220 Ma, which indicates that the deposition of the protoliths was active during the Late Triassic. Thesources areas for the detrital zircons are identified in the Malvinas Island, in the Deseado Massif, the erosion of the Eastern AndesMetamorphic Complex, the buried basement of Tierra del Fuego and outcrops in the Antarctic Peninsula. The cluster of Permian-Triassic ages may be related to the erosion of the volcanic arc emplaced along the western edge of Patagonia and AntarcticPeninsula, supporting the idea that Antarctic Peninsula was located in the southwestern edge of Southern Patagonia during thePermian-Triassic times. Despite the kind of basin in which the protoliths were deposited is unclear, the pattern of detrital zirconsallows us to infer a back-arc basin related to convergent settings as a possibly depositional environment, which is supported bythe petrography.